Analisis Faktor Yang Berhubungan Dengan Kesediaan Ibu Hamil Melakukan Tes Hiv Di Wilayah Kerja Upt Puskesmas Cimanggis Depok Tahun 2019 - Sumarno, Eni Ernawati; Sudiman, Herman; Widodo, Sri (LPPM Universitas Respati Indonesia, 2020)
ABSTRACT HIV/AIDS is a health problem throughout the world, including Indonesia. Data in 2018 pregnant women taking HIV in Indonesia as 5.291.143 people there were 761.373 pregnant women (13,38%) and 2.955 infected with HIV, have received ARV therapy 893 pregnant women and increased every year.. HIV testing during pregnancy is one way to prevent the transmission of HIV from mother to child. This study aims to determine the reasons behind the acceptance of pregnant women in undergoing HIV testing and the factors associated with the client willingness. This study was quantitative methods study design was cross sectional with independent variable and dependent variable, a large sample of 124 expectant mothers. Sampling use purposive sampling with predetermined inclusion dan exclusion criteria. Data were collected by interviews using a structured questionnaire. Data Population use univariate data analysis, bivariate chi-square test and multivariate analysis with logistic regression was used to assess findings.The results showed that the majority of respondents (66,9%) would be willing to test for HIV. Factors associated with the acceptance of HIV testing by expectant mothers were knowledge of HIV/AIDS (OR= 4,790), employment status (OR=1,795), frequency of ANC (OR=1,332), gestational age (OR = 1,323) and husband support (OR=0,538). Factors of age, education, attitude, parity, fellow pregnant mothers support, health workers support and service access were not significantly associated with acceptance of HIV testing by expectant mothers.The conclusions of the study is factors associated with the acceptance of HIV testing by expectant mothers were knowledge of HIV/AIDS, employment status, frequency of ANC, gestational age and husband support. Keywords : willingness of HIV testing, expectant mothers, cimanggis, depokReferences : 34 (2009-2018)